Improvement of the hematologic toxicities of ruxolitinib in patients with MPN-associated myelofibrosis using a combination of thalidomide, stanozolol and prednisone. Issue 1 (1st January 2019) - Duan, Minghui; Zhou, Daobin
ABSTRACT: Objective: Anemia and thrombocytopenia are the most frequently reported adverse events of ruxolitinib in patients with MPN-associated myelofibrosis (MPN-MF). Although thalidomide, androgens and prednisone have previously demonstrated improvements in myelofibrosis-associated anemia, it is unclear whether these drugs are effective in patients taking ruxolitinib. Method: We conducted a retrospective cohort study to evaluate the efficacy and tolerability of combination therapy with low dose thalidomide, stanozolol and prednisone (TSP) in patients with IPSS intermediate-2 or high-risk myelofibrosis (MF) who received ruxolitinib treatment. Results: Sixty-five patients with MPN-MF who took ruxolitinib were enrolled in this retrospective study, of which 46 patients also took TSP while 19 did not take TSP (TSP and non-TSP groups). Within the first 24 weeks, the proportion of patients with anemia response and platelet count increase ≥50 × 10 9 /L were 45.7% and 67.4% in the TSP group as compared to 0% and 10.5% in the non-TSP group ( p  < 0.001). The mean hemoglobin level in the non-TSP group reached the nadir after approximately 12–16 weeks of therapy, but gradually increased in the TSP group. Conclusion: In summary, TSP regimen can improve anemia and thrombocytopenia during ruxolitinib treatment in patients with MPN-MF, and the associated adverse events were manageable.